Adsorption of Quadrupolar, Diatomic Nitrogen onto Graphitized Thermal Carbon Black and in Slit-Shaped Carbon Pores. Effects of Surface Mediation - D.D. Do; H.D. Do (Adsorption Science & Technology)
In this paper, we study the effect of solid surface mediation on the intermolecular potential energy of nitrogen, and its impact on the adsorption of nitrogen on a graphitized carbon black surface and in carbon slit-shaped pores. This effect arises from the lower effective interaction potential energy between two particles close to the surface compared to the potential energy of the same two particles when they are far away from the surface. A simple equation is proposed to calculate the reduction factor and this is used in the Grand Canonical Monte Carlo (GCMC) simulation of nitrogen adsorption on graphitized thermal carbon black. With this modification, the GCMC simulation results agree extremely well with the experimental data over a wide range of pressure; the simulation results with the original potential energy (i.e. no surface mediation) give rise to a shoulder in the neighbourhood of monolayer coverage and a significant over-prediction of the second and higher layer coverages. The influence of this surface mediation on the dependence of the pore-filling pressure on the pore width is also studied. It is shown that such surface mediation has a significant effect on the pore-filling pressure. This implies that the use of the local isotherms obtained from the potential model without surface mediation could give rise to a serious error in the determination of the pore-size distribution.